Isang hambingang pagsusuri ng mga kaugalian sa pag-aasawa sa Camarines Norte at Batangas (lungsod ng Lipa, Malvar, Rosario, San Jose, at Tanauan) - Aboga, Angel Acero 1928- ([no publisher indicated], 1972)
The study is a contrastive analysis of the marriage outcomes of the people of Camarines Norte and Batangas. In this paper, the following topics were discussed: the characteristics of the youth in the two provinces, their courtship ways, their engagement, their betrothal and their marriage. Likewise, the superstitious beliefs which influences marriage and the level of society which has a direct bearing on the love affairs of the youth have been featured here. This analysis has revealed that the customs differ in the manner they are practiced, that the less related they are, the more problems there are, and that a number of Western culture borrowings have become a part of the marriage customs in Camarines Norte and Batangas.